2022
DOI: 10.1177/0095327x221100769
|View full text |Cite
|
Sign up to set email alerts
|

The Military Covenant, Contractual Relations, and Social Cohesion in Democracies: Estonia as an Exploratory Case Study

Abstract: The military covenant is a set of morally binding expectations marking the exchange between military, society, and the state. Its base is the military’s duality: like other large public institutions delivering services and its uniqueness in holding the monopoly over the use of legitimate organized state violence. The covenant is a form of relational (not transactional) contract based on trust between, and a long-term orientation of, partners; it both orders and displays these relations thereby offering both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…8 For example, in Switzerland, conscription promotes social and linguistic integration in a multicultural and multilingual society, thus holding historical and social significance for the Swiss military (Szvircsev Tresch, 2011). Similarly, conscription in Estonia, where around one third of the population is Russian-speaking, facilitates social cohesion and inclusion for the Russian-speaking minority through a shared sense of destiny, as the organisation transcends linguistic and social boundaries (Kasearu et al, 2022). However, studies have also indicated that Estonian-speaking conscripts have a higher likelihood of becoming non-commissioned officers (NCOs) compared to Russian speakers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 For example, in Switzerland, conscription promotes social and linguistic integration in a multicultural and multilingual society, thus holding historical and social significance for the Swiss military (Szvircsev Tresch, 2011). Similarly, conscription in Estonia, where around one third of the population is Russian-speaking, facilitates social cohesion and inclusion for the Russian-speaking minority through a shared sense of destiny, as the organisation transcends linguistic and social boundaries (Kasearu et al, 2022). However, studies have also indicated that Estonian-speaking conscripts have a higher likelihood of becoming non-commissioned officers (NCOs) compared to Russian speakers.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of conscription has a significant impact at both the social and individual level. Since conscription involves, directly or indirectly, large segments of the society contributing to the functioning of the armed forces and acts as a social contract in which everyone contributes to the defence of the state (Choulis et al, 2021;Kasearu et al, 2022), conscription generally has stronger public support (Choulis et al, 2021;Finnish ABDI, 2022;Forsvaret, 2021;Szvircsev Tresch et al, 2020;Turu-uuringute AS, 2020), and a higher will to fight 5 (Finnish ABDI, 2022;Rowe, 2002;World Value Survey, 2015 when compared to AVFs (see Figure 1).…”
Section: Characteristics Of Conscription In Six European Countriesmentioning
confidence: 99%
“…Some countries employ policies mandating certain levels of civic participation or knowledge about the national culture. For instance, various European countries mandate that migrants complete civic integration tests [42], while others require its citizens to complete military or civic service [43]. Other 'softer' policies concerning social cohesion tend to target areas such as employment, social protection, education and civic participation [26,44].…”
Section: Social Cohesion Within Policy and Politicsmentioning
confidence: 99%